2017
DOI: 10.1007/s12275-017-6350-6
|View full text |Cite
|
Sign up to set email alerts
|

Fungal diversity in soils across a gradient of preserved Brazilian Cerrado

Abstract: The preserved Cerrado from Northeastern Brazil presents different physicochemical properties and plant diversity, which can influence the fungal communities. Therefore, we evaluated the fungal diversity in preserved sites, at Sete Cidades National Park, across a gradient of vegetation that included Campo graminoide, Cerrado stricto sensu, Cerradao, and Floresta decidual. Of all of the operational taxonomic units (OTUs) obtained, the Floresta decidual presented the highest richness. Ascomycota were the most abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…This is in line with patterns observed for other microbiome components, i.e. bacteria 13 , 15 , 18 , archaea 16 and fungi 17 , 18 . These patterns can be attributed to abiotic differences, such as lower fertility and soil moisture, but higher acidity and soil temperature, in the grass compared to the tree zone.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is in line with patterns observed for other microbiome components, i.e. bacteria 13 , 15 , 18 , archaea 16 and fungi 17 , 18 . These patterns can be attributed to abiotic differences, such as lower fertility and soil moisture, but higher acidity and soil temperature, in the grass compared to the tree zone.…”
Section: Discussionsupporting
confidence: 89%
“…These patterns can be attributed to abiotic differences, such as lower fertility and soil moisture, but higher acidity and soil temperature, in the grass compared to the tree zone. Abiotic differences were shown to drive above-ground plant community-dynamics across the Cerrado 39 , 40 , and therefore likely also belowground communities 13 , 16 , 17 . In line with other studies, we show that a combination of multiple abiotic factors drive protist communities, with soil moisture being the principle factor 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the impact of fires on treegrass coexistence has thoroughly been studied (Bond et al, 2005;N'Dri, 2012;Sankaran et al, 2008). The impacts of fires on both soil properties and soil microorganisms are also widely acknowledged but have not been fully documented especially in African savannas (but see Belmok et al, 2019;Ferreira De Araújo et al, 2017). In the long-term, the cumulative short-term impacts of fires on mineral nutrient, C cycling and plant growth alter soil organic C concentration, pH, mineral nutrient concentrations, texture and structure, and water infiltration (Francos et al, 2018).…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…The diversity index values suggested by Ferreira de Araujo et al, 41 were higher than the ones shown by 53. Pereira de Castro et al, 42 and a higher fungal diversity was observed in campo graminoide than in Cerrado forests.…”
Section: Cerradomentioning
confidence: 58%